Perencanaan Sistem Penjualan Menggunakan TOGAF Architecture Development Method (TOGAF-ADM) Studi Pada PT. Millennium Pharmacon International Tbk Cabang Malang - Erzhal Risan Wikata; Nanang Yudi Setiawan; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
PT. Millennium Pharmacon International Tbk Malang is a distributor company which engaged in the field of pharmaceuticals such as medicines and medical equipment. From the business process that runs, there are some potential problems that disrupt the process of distributing goods. Out of stock of goods, stockpiling of goods, and long time processes also unoptimal archiving processes becomes the problem for the business process. It takes analysis and evaluation to maximize the company's performance in achieving the objectives as well as improving the business process. This research uses Business Process Modeling Notation (BPMN) and TOGAF Architecture Development Method (ADM) method to identify requirement, Fit / Gap analysis to analyze and evaluate business process and Business Process Reenginerin (BPR) to make improvement. From the results of simulations conducted on the current business process (As Is) to business process recommendations (To Be) on ordering goods found that Time Analysis incrase to 76,02%. Business process recommendations can minimize the problems that occur in the company. It can be concluded that the business process recommendation (To Be) can increase the added value for the company and activity that runs more effective and efficient.